1992
DOI: 10.1148/radiology.182.1.1727313
|View full text |Cite
|
Sign up to set email alerts
|

Childhood intussusception: US-guided hydrostatic reduction.

Abstract: Ileocolic intussusception is an important cause of acute abdomen in infants. When there is no surgical indication, reduction under fluorosco-pic vision has been the main radiologic treatment performed in our country. Ultrasound examination is broadly used as a diagnostic method but reports on local experiences with ultrasound for guidance in intussusception reduction have not been recorded. A series of five cases of successful hydrostatic reduction performed under ultrasonographic control is presented and imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
0
12

Year Published

1995
1995
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(54 citation statements)
references
References 0 publications
4
37
0
12
Order By: Relevance
“…The principal advantage of this technique is that the patient is not exposed to radiation. Sonographically guided hydrostatic enema may be performed with tap water, 16 saline solution, 8 or Hartmann's solution. 17 Many investigators have confirmed that this method is associated with a high success rate and very few complications.…”
Section: Discussionmentioning
confidence: 99%
“…The principal advantage of this technique is that the patient is not exposed to radiation. Sonographically guided hydrostatic enema may be performed with tap water, 16 saline solution, 8 or Hartmann's solution. 17 Many investigators have confirmed that this method is associated with a high success rate and very few complications.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound was found to be a reliable diagnostic screening modality in suspected cases of intussusception and ultrasound guidance is a promising technique for therapeutic reduction of intussusception. 2,13 . Thirty-two of our patients (53%) had surgical intervention with simple reduction in 22 patients (68.8%) and resection and anastomosis in 10 patients (31.2%).…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] This paper studies the clinical presentation and management of intussusception as seen at Maternity and Children's Hospital in Riyadh over a period of 2.5 years in infants and children.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrason eşliğinde ılık serum fizyolojikle redüksiyonda başarı %80 ve üzerinde olduğu bildirilmiştir. Kolay uygulanabilir olması ve hastanın radyasyona maruz kalmaması avantaj olarak vurgulanmıştır (23)(24)(25). Serum basıncı 75-125 mmHg arasında uygulanmıştır ve oluşan hidrostatik basıncın havanın basıncına göre daha düşük olması nedeniyle perforasyon riskinin az olacağı bildirilmiştir (26).…”
Section: Resimunclassified